The Impact of UI GreenMetric Involvement on Universities’ Performance in Shaping a Sustainable Campus - Sari, Riri Fitri; Suwartha, Nyoman; Setiani, Hastin; Sidiyanto, Yogi Andrian (Journal of Sustainability Perspectives, 2023)
UI GreenMetric was established before the initiative of the Sustainable Development Goals and other ranking to encourage universities in achieving sustainable development through their early awareness of environmental management on campus. In 2019, Times Higher Education launched a new ranking, namely the THE Impact Rankings, that assessed Sustainability progress implementation on campus. In this paper, we evaluate the impact of the consistency of university that have been participated in UI GreenMetric World University Rankings (UIGWUR) since 2010 to 2021. We evaluate 36 universities on the correlation between good performance in UIGWUR to the THE Impact ranking performed by 2019-2021. The results reveal that UI GreenMetric as an assessment tool, helped those universities in terms of shaping university readiness to achieve sustainable development. Those universities compete through annual reporting and the provided evidence of their progress on UI GreenMetric. Moreover, some universities have a high commitment to become sustainable campus through participating in sustainability-related rankings to monitor their progress regardless of the ranking results.